2000
DOI: 10.1046/j.1365-2265.2000.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in steroidogenic enzymes in human postnatal adrenal cortex: immunohistochemical studies

Abstract: Adrenarche is considered to occur as a result of intra-adrenal changes in steroidogenic enzymes involved in C19 steroid production. The present study was conducted because developmental changes in steroidogenic enzymes have not been examined well in human postnatal adrenal. Twenty-four specimens of nonpathological human adrenals from 7 months to 62 years retrieved from autopsy files. Immunohistochemistry for P450 side-chain cleavage (P450scc), 17alpha hydroxylase (P450c17), dehydroepiandrosterone sulfotransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
173
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 192 publications
(185 citation statements)
references
References 40 publications
10
173
1
1
Order By: Relevance
“…1). In these preadrenarchal infants, there is a poorly developed adrenal reticularis that does not express the enzymes needed to maintain high levels of DHEA-S production (Dhom, 1973;Suzuki et al ., 2000). Dhom (1973) observed that children at about age 3 had adrenals with only focal islands of zona reticularis, while a continuous reticularis did not begin until age 6, coinciding with detectable increases in circulating DHEA-S.…”
Section: Histological Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). In these preadrenarchal infants, there is a poorly developed adrenal reticularis that does not express the enzymes needed to maintain high levels of DHEA-S production (Dhom, 1973;Suzuki et al ., 2000). Dhom (1973) observed that children at about age 3 had adrenals with only focal islands of zona reticularis, while a continuous reticularis did not begin until age 6, coinciding with detectable increases in circulating DHEA-S.…”
Section: Histological Observationsmentioning
confidence: 99%
“…Although CYP11A is essential for DHEA-S biosynthesis and for adrenarche, all steroid hormone production requires CYP11A as well. In addition, the expression of CYP11A appears to be similar in all three zones of the adrenal cortex, and there are no changes in adrenal reticularis expression of CYP11A seen at adrenarche (Suzuki et al ., 2000). However, as CYP11A (with StAR) is the quantitative regulator of steroidogenesis, alterations in CYP11A activities may contribute to the genesis of premature and /or exaggerated adrenarche.…”
Section: Cyp11a (Cytochrome P450scc; Side-chain Cleavage Enzyme)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence suggests that adrenarche is a continuous process beginning in utero or at birth (Remer et al 2005). Once again, ZR development of DHEA production by CYP17 in the adrenal cortex is associated with both a reticularis-specific increase in cyt b5 expression while 3β-HSD expression decreases (Endoh et al 1996, Gell et al 1996, Suzuki et al 2000. Adrenarche precedes puberty, and the two processes are thought to be independent.…”
Section: Introductionmentioning
confidence: 99%